2013
DOI: 10.1108/03090561311324237
|View full text |Cite
|
Sign up to set email alerts
|

The impact of online user reviews on cameras sales

Abstract: PurposeThe purpose of this research is to help better understand the impact of online user reviews on sales of search goods.Design/methodology/approachThis research is based on digital camera sales data collected from amazon.com and two studies are included in this research. The first study is based on a static model and sample data from one time stamp. The second study is based on two sample data collected from two different time stamps, and a dynamic model is proposed.FindingsThe results from the first study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(34 citation statements)
references
References 21 publications
1
26
0
7
Order By: Relevance
“…Specifically, the effect of eWOM volume on sales is greater for mass products, while the effect of valence is greater for niche products. Zhang et al [46] have studied the impact of the online reviews on camera sales and found that a greater number of reviews and a greater review rating significantly improve sales, while [47] showed that the average reviews rating have a positive effect on hotel bookings. It is also worth mentioning the research of [48], which shows that the online review ratings for movies can predict the box office sales.…”
Section: Ewom and Salesmentioning
confidence: 99%
“…Specifically, the effect of eWOM volume on sales is greater for mass products, while the effect of valence is greater for niche products. Zhang et al [46] have studied the impact of the online reviews on camera sales and found that a greater number of reviews and a greater review rating significantly improve sales, while [47] showed that the average reviews rating have a positive effect on hotel bookings. It is also worth mentioning the research of [48], which shows that the online review ratings for movies can predict the box office sales.…”
Section: Ewom and Salesmentioning
confidence: 99%
“…Historical sales, price, and shipping cost [3,25,51] are also included as control variables in this study. In summary, customers pay attention to OED, which is expected to influence the customers' attitude toward products, and then lead to high sales for online sellers.…”
Section: Reputation Of Online Sellersmentioning
confidence: 99%
“…There is evidence to suggest that emotional involvement moderates the level of consumer product knowledge (Bloch, 1981;Zhang et al, 2013), not the in-depth technical knowledge associated with experts, but more from the aspect of interest in what it does rather than how it works, yet there is a gap in current literature that measures this construct. Another aspect that is not utilised, is the previous exposure or familiarity that consumers have with current products.…”
Section: Introductionmentioning
confidence: 99%